Gender dynamics in seed systems development - Kramer, Berber; Galiè, Alessandra (International Food Policy Research Institute, 2020)
All agricultural production—whether of crops, trees, forages, livestock, or fish—starts with seeds, making seed security vital to food security. Seed security means that producers—smallholder farmers especially—have permanent and unrestricted access to adequate quantities of quality seed that is suitable to their agroecological conditions and socio-economic needs. Efforts to enhance seed security should be inclusive, without disparities related to income, social class, age, or gender. Yet, gender gaps reveal themselves across the seed system, including in the breeding, production, selection, and distribution stages, as well as in how the seeds are used and who reaps the benefits from this use.